2007
DOI: 10.1091/mbc.e07-04-0327
|View full text |Cite
|
Sign up to set email alerts
|

Tau Phosphorylation Sites Work in Concert to Promote Neurotoxicity In Vivo

Abstract: Tau is a microtubule binding protein implicated in a number of human neurodegenerative disorders, including Alzheimer's disease. Phosphorylation of serine-proline/threonine-proline sites, targeted by proline-directed kinases, coincides temporally with neurodegeneration in the human diseases. Recently, we demonstrated that this unique group of serines and threonines has a critical role in controlling tau toxicity in a Drosophila model of tauopathy. Here, we use a combination of genetic and biochemical approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 47 publications
7
135
2
Order By: Relevance
“…Moreover, some studies have also shown that abnormal tau phosphorylation precedes neuronal apoptotic death. 34,40 Interestingly, a recent work documented the involvement of another tau-phosphorylating kinase, glycogen-synthase kinase 3 beta (Gsk-3β), in cell cycle regulation. 41 In this study it was shown that inhibition of Gsk-3β attenuated the expression of cell cycleassociated proteins, such as pRb or cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have also shown that abnormal tau phosphorylation precedes neuronal apoptotic death. 34,40 Interestingly, a recent work documented the involvement of another tau-phosphorylating kinase, glycogen-synthase kinase 3 beta (Gsk-3β), in cell cycle regulation. 41 In this study it was shown that inhibition of Gsk-3β attenuated the expression of cell cycleassociated proteins, such as pRb or cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Human LRRK2 cDNA or carrying mutations G2019S, R1441C (substitution of arginine to cystine at amino acid 1441), G2385R (substitution of glycine to arginine at amino acid 2385), or G2019S-K1906M (substitutions of lysine to methionine at amino acid 1906 in G2019S) were subcloned into the N-terminally Flag-tagged GateWay pUAST vector, and the resulting constructs were injected into w 1118 embryos to generate transgenic flies. Flies lines used in this study are 109(2)80 (Gao et al, 1999), ppk-GAL4, Ig1-1 (Grueber et al, 2003), GAL80 ts (Suster et al, 2004), UASDscam(TM1)-GFP (Soba et al, 2007), UAS-tauWT (Steinhilb et al, 2007), UAS-tau175/181 (Steinhilb et al, 2007), UAS-tau212 (Steinhilb et al, 2007), UAS-tau214 (Steinhilb et al, 2007), UAS-tau-RNAi (Vienna Drosophila RNAi Center), UAS-tauGFP (Murray et al, 1998), UAS-Syt-GFP (Estes et al, 2000), UAS-sggWT (Jia et al, 2002), UAS-sggDN (Jia et al, 2002), and sgg null (Bloomington Drosophila Stock Center). Antibodies for Western blots, immunoprecipitation, and immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore important to examine whether G2019S affects the phosphorylation status of tau. Antibodies that specifically recognize phosphorylated serine-proline or threonineproline sites of tau were used, including AT270 (pT175/pT181), AT8 (pS202/pT205), and AT100 (pT212/pS214) (Steinhilb et al, 2007). Western blots show that the phosphorylation levels of tau protein at T175/T181 and S202/T205 sites are unaltered by neuronal expressions of wild-type and mutant LRRK2 transgenes, compared to the elav-GAL4 GAL4 driver alone (Fig.…”
Section: The Human Tau T212a Phosphomutant Suppresses G2019s-induced mentioning
confidence: 99%
“…Ser 238 and Thr 245 have actually been reported phosphorylated in samples from human AD patients by mass spectrometry (Sergeant et al, 2008), suggesting that they may play a role in neuronal dysfunction or degeneration. Nevertheless, these are novel sites because they have not been studied functionally and were not altered in the 0N4R E14 (Khurana et al, 2006), 0N4R AP (Steinhilb et al, 2007a), or 2N4R S11A (Chatterjee et al, 2009) transgenes. Therefore, we changed these two amino acids in a FLAG-tagged WT 2N4R hTau to nonphosphorylatable alanines yielding the 2N4R-STA FLAG-tagged protein.…”
Section: Novel Mutations On 2n4r Htau Suppress Toxicity But Yield Dysmentioning
confidence: 99%